2003
DOI: 10.1177/1052562903252520
|View full text |Cite
|
Sign up to set email alerts
|

A Capstone Project in Business Ethics: Building an Ethics Training Program

Abstract: This exercise for teaching business ethics is industry-specific, challenging, and requires direct student participation. Specifically, student groups are asked to develop an ethics training session for a business with an accompanying training manual. The exercise involves a comprehensive description of ethical issues in a particular industry, possible causes of unethical behaviors, sources for information on ethical issues, and linkages to corporate codes of ethics. A discussion of the exercise's potential ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Little evidence supports the notion that MBA students who take ethics courses will make ethical decisions (Evans et al, 2006;Weber, 1990). Although teaching ethics is important and worthwhile and will cause some students to move in the right and ethical direction (e.g., Gautschi and Jones, 1998;Giacalone et al, 2003;Hiltebeitel and Jones, 1992;Jurkiewicz et al, 2004), teaching students the rules and guidelines of a particular profession to achieve a certification or license (e.g., accounting) will not ensure students' ethical actions (Luoma, 1989). A course on ethics produces either no significant effect (e.g., Davis and Welton, 1991;Peppas and Diskin, 2000), limited effect on students' attitudes toward ethical decisions (e.g., Duizend and McCann, 1998), or limited effect for females only (not for males) (Ritter, 2006).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Little evidence supports the notion that MBA students who take ethics courses will make ethical decisions (Evans et al, 2006;Weber, 1990). Although teaching ethics is important and worthwhile and will cause some students to move in the right and ethical direction (e.g., Gautschi and Jones, 1998;Giacalone et al, 2003;Hiltebeitel and Jones, 1992;Jurkiewicz et al, 2004), teaching students the rules and guidelines of a particular profession to achieve a certification or license (e.g., accounting) will not ensure students' ethical actions (Luoma, 1989). A course on ethics produces either no significant effect (e.g., Davis and Welton, 1991;Peppas and Diskin, 2000), limited effect on students' attitudes toward ethical decisions (e.g., Duizend and McCann, 1998), or limited effect for females only (not for males) (Ritter, 2006).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Some full-time MBA students are required to visit federal prisons and interview white-collar criminals who are paying their dues to society -often for cooking the books (Kercheval, 2004;Merritt, 2004). Business schools must seek the best balance between theory and practice and may want to adopt experiential approaches that involve students more deeply and create stronger impacts on ethics than other methods (e.g., Giacalone et al, 2003;Jurkiewicz et al, 2004).…”
Section: Future Researchmentioning
confidence: 99%
“…Burton, Johnston, and Wilson (1991) provided some empirical evidence that class discussion of business scenarios, instead of lectures about ethics, coupled with a neutral instructor stance during such discussions, can increase student thinking about, and sensitivity to, ethical issues in workplace situations. Although Giacalone et al (2003) pointed out the limitations of "experiential exercises" in satisfying students' desires for practical workplace skills, such exercises do seem to satisfy the authors' call for the "real-world examples" they found essential in ethics teaching (p. 598).…”
mentioning
confidence: 95%
“…Indeed, faculty members could assess students' learning of ethics-related goals by reading their written submissions. We are aware of only one other published business ethics capstone, that of Giacalone et al (2003). In Giacalone et al's (2003) exercise, students develop an ethics training session and manual.…”
Section: Capstone Exercisementioning
confidence: 99%